A critique of the active ageing index - São José, José (2019)
Active ageing and successful ageing are ubiquitous concepts in contemporary societies. In the European Union, active ageing is monitored and promoted chiefly by the Active Ageing Index, a policy tool in use since 2012. We acknowledge that the MI may contribute to sensitizing people, including policymakers, to the multidimensionality and complexity of the process of "ageing well". However, we note that despite being widely used and promoted, the Active Ageing Index remains under-scrutinized. In this article, we undertake a comprehensive critical analysis of the Active Ageing Index. This critical analysis is supported by the Theory of Model Ageing, the Capability Approach and, to a lesser extent, by relevant literature on composite indices. We conclude that the Active Ageing Index was developed with the paradoxical aim of deriving "the solution" from "the problem". It is an under-theorized and narrowly conceptualized index that contributes to the process of Model Ageing, as its conceptual foundation, and its domains and indicators, convey a certain model of active ageing. This model is expert-based and ingrained with a priori assumptions about the potential of older people, the domains of life and activities they value and how strongly they value them. Finally, the Active Ageing Index measures current achievements, not capabilities (i.e. the opportunity set of achievable "doings" and "beings"), resulting in a valuable but incomplete tool for policymaking purposes. We hope that this critical analysis will initiate a debate on the Active Ageing Index that, in our view, is overdue. (C) 2017 Elsevier Inc. All rights reserved.